Sesión de Retórica: Espacio de Encodificación - Romero Farfán, César Augusto (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The topic of this article is an "Interuniversity Session of Rhetoric". It comes from a pedagogic strategy consisting of a group of students that persuasively presented linguistic theories to a group of contemporaries to try to internalize them. It is possible to apply this strategy in different classes or courses to strengthen analysis, memorization, documentation, oral and written skills, and the ability of conviction and persuasion in basic education or high education. The writing can be extended, for example, to establish how an interuniversity session of rhetoric consolidates teamwork. Finally, this article concludes on how the session of rhetoric is, definitely, a space to encode attitudes and knowledge.